IMPLEMENTASI E-MODUL BERBASIS MULTIMEDIA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: STUDI KUALITATIF TERHADAP KETERLIBATAN SISWA - Anisa Anisa; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to describe the implementation of multimedia-based e-modules in Islamic Religious Education (PAI) learning and to analyze their impact on student engagement. A qualitative descriptive approach was employed, involving observation, in-depth interviews, and documentation with teachers and students at the junior secondary school (MTs) level. The implemented e-modules included interactive content such as videos, animations, digital quizzes, and external links designed to support conceptual understanding. The findings reveal that the use of multimedia-based e-modules enhances students’ active participation, strengthens conceptual comprehension, and fosters a more engaging and contextual learning experience. Student engagement was evidenced by their enthusiasm in discussions, increased frequency of questions, and ability to independently complete digital-based assignments. These results affirm that integrating multimedia technology into PAI instruction serves as an effective strategy to holistically promote student engagement.